Impact of Fiscal Balance Fund Transfer Policies on Economic Growth Convergence in Indonesia - Arfiyansyah, Sintong; Budi Santoso, Dwi; Pangestuty, Farah Wulandari (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2025)
Research Originality — This research aims to analyze how fiscal balance transfers impact the acceleration of economic growth convergence in the country. Convergence means that more regions can enjoy economic growth. Research Objectives — The research used secondary data from 2015 to 2022 and focused on 34 provinces in Indonesia. Research Methods — This study employs a quantitative research design, with a convergence analysis framework based on panel data regression. The empirical model uses both absolute and conditional convergence methodologies to investigate the relationship between regional income levels and fiscal transfer policies. The analysis is based on secondary data from 34 Indonesian provinces between 2015 and 2022. The main explanatory variables are the per capita realizations of General Allocation Funds (DAU), Special Allocation Funds (DAK), and Revenue Sharing Funds (DBH). The fixed effects estimator is used to correct for unobserved heterogeneity, and the Hausman test is performed to assess the validity of the model definition Implications — The central government needs to exercise vigilance in respect of the allocation of balance funds because DAK has not been able to contribute to the economic growth in Indonesia. Regional governments also need to exercise vigilance and have strong controls in using balance funds. Better planning of balance funds, which are purpose grants, needs to be facilitated through efficient spending planning and synchronized with national priorities, ensuring that balance funds can be properly absorbed by regional governments and have an impact on economic development in each region.